(untitled) - Pomponio, Arthur T. (New York, 2002)
On September 11, 2001 several acts of violent terrorism profoundly and permenently affected the way U.S. citizens live their lives. Terrorism, long a problem in other parts of the world, came to our shores. Not only have many of us experienced trauma, but now we must acknowledge the on-going stresses associated with possible future acts of terrorism. A new and most unwelcome reality has been thrust upon us and we must learn to cope with it. Psychological Consequences of Terrorism offers the reader a start. This supplementary text provides a brief explanation of how the trauma from terrorist acts affects the way we think, feel, and act. It addresses such important topics as stress, trauma, anxiety and grief. A vignette from an actual support counseling group helps readers to see that they are not alone in their emotional reactions to the current events. The text also offers readers practical information about how to help themselves and their loved one cope with the ensuing stress. Numerous Active Learning Activities help readers to apply what they learn to their own lives.
Keywords: Terrorism